(untitled) (Eurasian Scientific Herald, 2022)
The article considers about internet as a resource for teaching and learning. It defines the didactic functions of the Internet for the subject "foreign language", the purposes of using the Internet for learning a foreign language, as well as the possibility of using the Internet as a learning tool.